Register based study of anorectal anomalies over 26 years: Associated anomalies, prevalence, and trends. Issue 7 (14th July 2015) - Godse, Alok S.; Best, Kate E.; Lawson, Anne; Rosby, Lucy; Rankin, Judith
Abstract : BACKGROUND: Anorectal anomalies are atresias or stenoses of the anal canal and rectum with or without fistulous connections with the bladder, urethra, perineum, or vestibule. The aim of this study was to describe the epidemiology of anorectal anomalies, including associated anomalies, prevalence, and temporal trends. METHODS: Anorectal anomalies occurring in late miscarriages (>20 gestation weeks), terminations of pregnancy for fetal anomaly (any gestation), stillbirths (≥24 gestation weeks) and live births, delivered from 1985 to 2010, notified to the Northern Congenital Abnormality Survey (NorCAS) were included in this population‐based case series. RESULTS: There were 278 cases among 892, 194 live births. Twenty (7.2%) cases occurred in twin pregnancies and 24 (8.7%) with chromosomal anomalies/genetic syndromes were excluded. There were 234 cases (total prevalence = 2.7, 95% confidence interval [CI]: 2.4, 3.1 per 10, 000 live and stillbirths). There was no evidence of a trend in prevalence over time (Chi 2 test for trend: p = 0.789). There was a male predominance (70.9%). Of the 234 cases, 167 (71.4%) were live born, two (0.9%) were late miscarriages, seven (3.0%) were stillbirths, and 58 (24.8%) were terminations of pregnancy for fetal anomaly. There was no significant association with maternal age at delivery ( p = 0.095). 7.2% of isolated cases (cases with no other congenital anomalies) were diagnosed prenatally. CONCLUSION: The prevalence of anorectal anomalies in this study is comparable to other case series. There was no evidence of a temporal increase in prevalence. We confirmed a male predominance of anorectal anomalies and no significant association with maternal age. Birth Defects Research (Part A) 103:597–602, 2015. © 2015 Wiley Periodicals, Inc.